Analisis Dan Perancangan Sistem Informasi Manajemen Anggaran Pada Dinas Pendidikan Provinsi Jambi - Irawan, Asdi; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2020)
Every organization or plan needs to create an information system in order to support all activities so that the information generated can be carried out quickly and accurately. One of the information needed is information about the budget owned by an organization or authority. The issue of budget extraction in every expenditure, government expenditure becomes an important factor to stimulate a budget that adheres to the principles of budget savings, efficient and effective. The Jambi Provincial Education Office is a Regional Apparatus Organization (OPD) within the Jambi Provincial Government Environment which is responsible for education by the Governor through the Jambi Provincial Regional Secretary. Therefore the Thesis Report with the title